Jaws [videorecording (DVD)] - Spielberg, Steven, 1946-; Dreyfuss, Richard; Scheider, Roy; Shaw, Robert, 1927-1978; Benchley, Peter (Universal Home Video, 2012)
When the seaside community of Amity finds itself under attack by a dangerous great white shark, the town's chief of police, a young marine biologist, and a grizzled shark hunter embark on a desperate quest to destroy the beast before it strikes again.